Andaliman (Zanthoxylum acanthopodium DC.) fruit ethanolic extract exerts attenuative effect on hyperglycemia, sensory and motoric function’s disorders in alloxan-induced diabetic mice - Santoso, Putra; Simatupang, Arin Saparima; Fajria, Annisha; Rahayu, Resti; Jannatan, Robby (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Andaliman (Zanthoxylum acanthopodium) is a potent medicinal plant in Asia. This present study aimed to reveal the effectivity of Andaliman fruit extract in alleviating hyperglycemia, sensory and motoric balance disorders, histopathology of the cerebellum, and tissue oxidative stress in diabetic mice induced by alloxan. Materials and Methods: Diabetes induction was performed by intraperitoneally injecting alloxan monohydrate [200 mg/kg body weight (BW)]. Subsequently, the mice were treated daily with an ethanolic extract of Andaliman fruit (0, 150, 300, 450 mg/kg BW per oral) for 28 days, followed by measurements of blood glucose, paw sensitivity, motoric balance, histopathology of the cerebellum, and malondialdehyde (MDA) levels. Moreover, the phytochemical constituents of the extract were elucidated by liquid chromatography. Results: Higher doses of Andaliman fruit extract could significantly attenuate the elevation of random and fasting blood glucose (p < 0.05) and improve paw sensitivity responses (p < 0.05) and motoric balances (p < 0.05) in diabetic mice. Moreover, Andaliman fruit extract could significantly attenuate the degeneration of cerebellar Purkinje cells (p < 0.05) and suppress MDA levels in the blood (p < 0.05) while blunting the MDA in the brain tissue (p < 0.05). Phytochemical screening revealed 39 compounds in the Andaliman extract belonging to the groups of alkaloids (26 compounds), flavonoids (12 compounds), and terpenoids (1 compound). Conclusion: The ethanolic extract of Andaliman fruit is capable of ameliorating diabetic neuropathy, motor balance disorders, and Purkinje cell degeneration while also reducing oxidative stress in the peripheral system. Hence, Andaliman extract is a promising candidate for formulation as an herbal remedy against the detrimental outcomes of diabetes mellitus. J. Adv. Vet. Anim. Res., 10(4): 608–619, December 2023 http://doi.org/10.5455/javar.2023.j716